Treatment Outcomes in Advanced Biliary Tract Cancers: Single Institution Retrospective Analysis - Nikhil Pathi; Senthil J. Rajappa; Santa Ayyagari; M V. T. Krishna Mohan; Pavan Kumar; Rakesh Pinninti; Pallavi Ladda; Sanath Kandem; Rohan Tewani; Kinjal Shah; Kripa Bajaj; Sree Rama Krishnaiah; et al. (Indian Journal of Medical and Paediatric Oncology, 2025)
Purpose Biliary tract cancers (BTCs), particularly gallbladder cancers (GBCs), are prevalent in India. Yet there are limited data on treatment outcomes. To bridge this gap, we performed an analysis of advanced BTC treatment outcomes at our institute, seeking to offer insights into real-world scenario.